Natalie Abell, Keos XII. Ayia Irini: Area B. - Dickinson, Oliver (Journal of Greek Archaeology, 2023)
pp. xviii+360, 52 plates (5 col.), 52 B/W figures, 35 tables. Atlanta: Lockwood Press, 2021 ISBN 9781948488570 (hardback), 9781948488679 (pdf). 80.